GAYA KEPENGARANGAN DEWI LESTARI DALAM NOVEL SUPERNOVA: KESATRIA, PUTRI, DAN BINTANG JATUH - Vera Soraya Putri; Endang Sri Widayati; Furoidatul Husniah (Fakultas Bahasa dan Seni UNP, 2019)
Dewi Lestari has a distinctive authorship in Supernova: Kesatria, Putri, dan Bintang Jatuh novel. This particularity can be seen in the construction of content and the use of linguistic aspects as a means of delivering ideas by Dewi Lestari. This research aims to describe the construction of themes and characters, and the form of linguistic aspects as Dewi Lestari's authorship in the Supernova: Kesatria, Putri, dan Bintang Jatuh novel. This research used descriptive-qualitative, and used stylistic approach. The finding of the research showed Dewi Lestari's authorship style in Supernova: Kesatria, Putri, dan Bintang Jatuh novel is